2014
DOI: 10.5704/moj.1407.013
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular nodular Fasciitis: An unexpected Diagnosis for a Joint lesion: A Case report

Abstract: Pathological lesions in and around a joint can arise from underlying dermis, subcutis, deep muscle, bone or synovium. Clinical presentation can include joint pain, joint swelling, palpable masses and mechanical restriction. Whilst giant cell tumour of tendon sheath, pigmented villonodular synovitis, synovial chondromatosis, lipoma arborescens, juxta articular myxomas and inflammatory arthritis are the better-known conditions of the joint. Intra-articular nodular fasciitis, on the other hand, is less well recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Nodular fasciitis has been reported in joints, most commonly in the knee joints, and has been diagnosed solely on the basis of morphology. [3][4][5][6]8,11,15,17] Only three cases of nodular fasciitis in the elbow joint have been reported to date. [17][18][19] This case is the rst to con rm the diagnosis of nodular fasciitis within the elbow joint by demonstrating gene rearrangement of USP6-MYH9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nodular fasciitis has been reported in joints, most commonly in the knee joints, and has been diagnosed solely on the basis of morphology. [3][4][5][6]8,11,15,17] Only three cases of nodular fasciitis in the elbow joint have been reported to date. [17][18][19] This case is the rst to con rm the diagnosis of nodular fasciitis within the elbow joint by demonstrating gene rearrangement of USP6-MYH9.…”
Section: Discussionmentioning
confidence: 99%
“…While recent reports have described nodular fasciitis arising within joints, this is an exceedingly rare occurrence. [3][4][5][6][7][8][9][10][11][12][13][14][15] Diagnosing nodular fasciitis in an uncommon location can be challenging for pathologists. It has been shown that the USP6-MYH9 fusion is present in up to 92% of nodular fasciitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…The differential diagnosis included intra-articular PVNS, juxta-articular myxomas, synovial chondromatosis, lipoma arborescence, fibroma of the tendon sheath, ganglion cyst, desmoid tumor, and hemangioma. Intra-articular nodular fasciitis is rarely encountered, and therefore, is not usually considered during the clinical investigation of joint symptoms [9].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical findings (site, follow up, and recurrence) of intra-articular fasciitis are summarized in Table 1 from 17 case reports [1,2,4,6,7,[10], [11], [12], [13], [14], [15], [16], [17], [18], [19]]. The prognosis of the condition is excellent and local recurrence of the lesion was not observed among the previously reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nodular fasciitis, knee pain may also arise from other diseases such as synovial chondromatosis, pigmented villonodular synovitis or giant cell tumour of the tendon sheath. We report a case of intra-articular nodular fasciitis in this study, and describe the clinical, radiological and pathological features of 21 previous case reports [1021].…”
Section: Introductionmentioning
confidence: 88%